Centuries-Long Trends in the Linguistic Integration of Croatian Society - Amir Kapetanović (Slovene, 2012)
The article discusses the history of the Croatian language, particularly the paths of the gradual linguistic integration of all Croats and the development of the standard language (based upon the Štokavian dialect) within Croatian society, whose members have spoken three dialects (Čakavian, Štokavian, Kajkavian) since the Middle Ages. Because of the multidialectal situation (all three dialects played an important role in the history of the Croatian language), linguistic integration was a complex process. The use of the Croatian language before national integrality in the 19th century may look complicated and disunified, but this article attempts to show the old connections between different dialectal areas and the realization of two the main conceptions of the construction of Croatian superdialectal (literary) expression in linguistic history: a literary language with a single-dialect basis (but with multi-dialectal infiltration within the superstructure) and a literary (hybrid) type of language based upon at least two dialects.